2022
DOI: 10.1093/milmed/usac093
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Reconstruction Surgery: Creating a Permissive Healing Phenotype in Military Personnel and Civilians for Faster Recovery

Abstract: Introduction Anterior cruciate ligament (ACL) rupture in military personnel and civilians can be a devastating injury. A service member is 10 times more likely to suffer an ACL injury than their civilian counterparts, and despite successful surgical stabilization, 4%-35% will develop arthrofibrosis, over 50% will not return to full active duty, and up to 50% will develop post-traumatic osteoarthritis (PTOA) within 15 years. Equally concerning, woman are 2 to 8 times more likely to experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…The effect of sex on joint tissue repair processes following an ACL rupture are poorly understood ( 2 ). We report in a rat model of non-surgical ACL rupture: (1) both sexes showed similar functional responses early after ACL rupture, however, females had persistent mechanical hyperalgesia; (2) males and females showed different hematological and systemic inflammatory responses over 31-days; (3) males had significantly higher levels of VEGF, RANTES and IP-10 chemokines in synovial fluid compared to females; (4) Acta2 gene expression (α-SMA production) in the ACL remnant was significantly higher in males with no change in females; and (5) sex differences in ECM remodeling were also apparent in the IFP and articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The effect of sex on joint tissue repair processes following an ACL rupture are poorly understood ( 2 ). We report in a rat model of non-surgical ACL rupture: (1) both sexes showed similar functional responses early after ACL rupture, however, females had persistent mechanical hyperalgesia; (2) males and females showed different hematological and systemic inflammatory responses over 31-days; (3) males had significantly higher levels of VEGF, RANTES and IP-10 chemokines in synovial fluid compared to females; (4) Acta2 gene expression (α-SMA production) in the ACL remnant was significantly higher in males with no change in females; and (5) sex differences in ECM remodeling were also apparent in the IFP and articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior cruciate ligament (ACL) rupture is one of the most debilitating musculoskeletal injuries and typically occurs following excessive rotational stresses and/or extreme deceleration forces (1,2). Globally, there are over 2 million ACL injuries each year, with annual incidence rates continuing to rise, particularly in the young (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The patient who demonstrates significant fear may benefit from postponing the protocol's progression, receiving information to boost patient self-efficacy, and implementing neuromuscular re-education approaches such as perturbation training. It has been demonstrated that kinesiophobia and pain catastrophizing are two psychological characteristics significantly associated with not returning to sport [40,41] .…”
Section: Management Of Fearmentioning
confidence: 99%